"I’m strong within myself": Gender, class and emotional capital in childcare - Andrew, Yarrow (British Journal of Sociology of Education, 2015)
Emotions have received increasing attention in educational circles in the last decade. Drawing on Bourdieu, feminist scholars use emotional capital to illustrate the ways gendered inequalities can compound the disadvantages of social class. This paper examines relationships within childcare services in Australia, showing how emotional capital functions as a resource for staff. Data from interviews with childcare staff illustrate key aspects of emotional capital, such as reflexivity, resilience and embodiment. Findings show that investing in emotional capital is the key to a long-lasting commitment to childcare work, and should be valued accordingly. © 2013 Taylor & Francis.
Keywords: 2000 à aujourd'hui; 2010-2019; australie; capital émotionnel; care; discipline; maternité; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; service de garde; sociologie; thématiques; travail; travail du care